Paraphrasing Strategy in Enhancing the Student’s Reading Comprehension - Nirwana, Nirwana (JLE: Journal of Literate of English Education Study Program, 2020)
The objective of this study is to identify the implementation of the paraphrasing strategy for the students at Mts Ummul Mukminin Makassar in teaching reading comprehension and the interest in using that strategy in the teaching and learning process. 30 students for the experimental group and 30 students for the control group were involved in the subject. The resources consisted of a test for reading comprehension and a questioner.The result showed that paraphrasing strategy substantially improves the reading comprehension of the students (.000 < .05). The questionnaire was given to the students covered the statement about whether or not the students are interested in the use of paraphrasing strategy. The questionnaire result shows that the use of paraphrasing strategy in teaching reading improves their interest in reading comprehension. In other words, the students have high interest to the use of paraphrasing strategy in learning reading. The interest of the students was classified in high category for experimental community, which is shown by the mean interest of students 71.87. Finally, the paraphrasing technique leads to enhancing the achievement of reading comprehension and students are involved in using the strategy in the course of teaching and learning.